Fetichization and desfetichization of power in the work of Enrique Dussel: contributions to a positive analysis of power - Douglas Michel Capiotti; Antônio Gabriel Santana Martins (Dialogos, 2025)
The present article examines the fetishization of power in the works of Enrique Dussel. It aims to highlight the contributions of this Mexican-Argentine philosopher to key issues in Political Science and Marxism. Starting with the debate on power in the modern era and the adoption by leading Marxist thinkers of a negative hegemonic conception of power, the article explores the significant shift introduced by Enrique Dussel. He characterizes power as having two poles, emphasizing the singular relevance of the positive pole for those who aspire to human emancipation.